Analisis Nilai-Nilai Pendidikan Dalam Cerpen “Panglatu” Karya Tiflatul Husna - Marie Muhammad, Putri Juwita (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2022)
This study aims to describe the educational values ??contained in the Panglatu Karya Tiflatul Husna short story where the short story is the selected manuscript of the Harris & YBWS Firm's Short Story Creation Contest. , moral, social, cultural and aesthetics. The conclusion obtained from this study is (1) the value of the religious teaching us to trust God in granting a prayer request from his servant. (2) Moral values ??that teach us are always devoted to both parents and spread goodness to anyone, including those who disappoint us. (3) Social values ??teach us how concern between fellowness and always encourages and helps people who are experiencing distress. (4) cultural values ??which we can maintain and preserve. (5) Aesthetic values ??are beautiful sentences presented by the writer. From the whole that the educational values ??contained in the short story of Panglatu by Tiflatul Husna are a reflection and good picture in society. It's just that there are some problems that should not be imitated because they have very poor moral values.